2006
DOI: 10.1111/j.1574-6968.2006.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and structural analyses of the mating-type loci inClavicipitaceae

Abstract: Entomopathogens and other econutritional fungi belonging to Clavicipitaceae were phylogenetically analyzed on the basis of the 18S rRNA gene and mating-type genes (MAT1-1-1 and MAT1-2-1). The phylogenies of the mating-type genes yielded better resolutions than that of 18S rRNA gene. Entomopathogens (Cordyceps bassiana, Cordyceps brongniartii, Cordyceps militaris, Cordyceps sinclairii, Cordyceps takaomontana, Isaria cateniannulata, Isaria farinosa, Isaria fumosorosea, Isaria javanica, Lecanicillium muscarium an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 32 publications
1
55
1
Order By: Relevance
“…BLASTP and BLASTX analyses of the genomic region upstream of the idiomorph revealed the presence of a DNA lyase gene with highest homology to the M. fijiensis DNA lyase, both at the nucleotide (76% identity over 1,083 nucleotides) and the protein level (67% identity over 312 amino acids). The DNA lyase gene is commonly found upstream from the mating-type loci in other ascomycetes (8,33,36). Besides the DNA lyase gene, no other genes could be identified upstream from the mating-type loci (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…BLASTP and BLASTX analyses of the genomic region upstream of the idiomorph revealed the presence of a DNA lyase gene with highest homology to the M. fijiensis DNA lyase, both at the nucleotide (76% identity over 1,083 nucleotides) and the protein level (67% identity over 312 amino acids). The DNA lyase gene is commonly found upstream from the mating-type loci in other ascomycetes (8,33,36). Besides the DNA lyase gene, no other genes could be identified upstream from the mating-type loci (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At smaller geographic scales, Wen et al (2012) found that different monoconidial isolates showed genetic variation, consistent with genetic recombination and heterothallism of C. militaris (Table 1). The mating system in C. militaris is controlled by one locus with two alleles, MAT 1-1-1 and MAT 1-2-1 (Shrestha et al 2004; Yokoyama et al 2006; Zheng et al 2011). While natural fruiting bodies are formed from insects infected with heterokaryotic mycelia containing both mating types, fruiting bodies can also form on cereal substrate (Shrestha et al 2012).…”
Section: Macrofungi Parasitizing Animalsmentioning
confidence: 99%
“…The genus Ephelis has already been phylogenetically analyzed based on the sequences of rDNA-ITS regions and the mating loci with other Clavicipitaceae fungi 10,[35][36][37] . We elucidated that there existed two types in E. japonica isolates in results of PCR-RFLP.…”
Section: Ephelis Japonica Hennings (Hennings 1904)mentioning
confidence: 99%